Analysis of stepwise expression of sake fermentation broth - Fukuyama, Ryo; Ginting, Alvin Najmuddin; Tanaka, Takanori; Yabuta, Nobuyasu; Jami, Mohammed Saedi; Iwata, Masashi (2015)

(untitled)
In the sake brewing, expression is used for the separation of liquid from the fermentation broth. Although the period of expression has to be as short as possible in order to prevent the sake from losing flavour, practically it takes much time to complete expression because of the highly compressible materials (e.g. proteins and starch) in the broth. For the expression of highly compressible materials, it is known empirically that the applied pressure should be low at the beginning of the expression and increased stepwise as the expression proceeds. In this study, we propose a method for the analysis of stepwise expression of highly compressible materials. The fermentation broth of sake was used as the experimental material. The experimental apparatus of constant pressure expression utilised in this study essentially consists of a vertical cylinder with a movable piston. The change in thickness of the material in the cylinder with the time was measured by a dial gauge. The mechanism of liquid removal is filtration at the beginning of expression, followed by consolidation. The filtration rate can be obtained by applying Ruth’s constant pressure filtration theory. In the consolidation period (i.e. after the end of the filtration), the deliquoring rate is calculated by the numerical analysis of the basic consolidation equation. However, because the formula expressing the distribution of solid compressive pressure pS of a filter cake with highly compressible materials has not been established well, the consolidation equation cannot be solved analytically. We therefore propose a new empirical equation representing the pS-distribution of a filter cake with highly compressible materials. The equation proposed in this study makes it possible to analyse the stepwise expression of highly compressible materials.